Knowledge’s schemes of positive and negative self-talk learning styles in university students - Orellana Manrique, Oswaldo (2009)
The research is descriptive and comparative aims to disseminate the results of psychological research on mindsets of self-talk, positive and negative, and learning styles of students in San Marcos belonging to each of the five academic field organizing vocational training: Health Sciences, Basic Sciences, Engineering, Business and Humanities. For purposes of the study has used two instruments: (1) self-talk Inventory (Calvete, Esteve, Landin), comprising two subscales: positive and negative¸ both with the technical specifications in order to draw conclusions valid and reliable, so we the original statistics, alpha coefficients of 0.89 for negative self-talk scales and 0.86, 0.79 and 0.87 for the subscales of thoughts related to anxiety, depression and anger, respectively. On the other hand, the alpha coefficients were 0.82 for positive self-Scale and 0.72, 0.76 and 0.55 for the subscales of minimization, positive affect and coping self-talk, respectively, (2) Honey-Alonso Questionnaire Learning Styles (CHAEA) investigating four learning styles: active, reflective, theoretical and pragmatic, with consequent acceptance criteria, 0.84 (theoretical), 0.82 (reflective), 0.78 (pragmatic) and 0.74 (active).